Domestic Bond Market Development - Batten, Jonathan A. (World Bank, 2012)
A two-tiered approach to financial market development aimed at both bank and bond market reform would also be complementary to longer term economic development, provided services could be delivered through efficient financial and legal institutions (Chakraborty and Ray 2006) and there was strong protection for investors and sound fiscal and monetary policy management by government (Burger and Warnock 2006b). Historically, local issuers tend to issue in the major currencies (U.S. dollars, yen, and euro), and then either swap the proceeds into local currency (interest rate parity theory suggests this should deliver funds equivalent in yield to what is available in the domestic market) or, more often, sell the foreign currency proceeds in spot foreign exchange markets, leaving the repayment cash flows unhedged. Chakraborty and Ray (2006) recently established that although stronger bank monitoring helps to resolve information asymmetries and agency concerns, it is the efficiency of financial and legal institutions that influences growth outcomes, whether there is a bank- or a market-based financial system. Among them are the need for enabling regulation, including reform of withholding and other foreign investor taxes (Lejot, Arner, and Liu 2006); continuing reform of corporate governance, which includes better creditor rights, bankruptcy procedures, and contract enforcement (Beck, Levine, and Loayza 2000; Burger and Warnock 2006); and strong financial infrastructure for better information disclosure, the establishment of reliable credit ratings (Kisselev and Packer 2006) and robust benchmark yield curves The securities market is largely self-regulated through organizations such as the Korea Securities Dealers Association, the Korea Exchange, and the Korea Securities Depository, and four local agencies assign credit ratings: Korea Investor Service (a Moody's affiliate), Korea Ratings (a Fitch affiliate), National Information & Credit Evaluation, and Seoul Credit Rating & Information. This process began in 2004 with the introduction of the Korea Interbank Offered Rate (KORIBOR), which should become the benchmark interest rate for short-term financing for banks and may become a reference rate for bond or swap transactions. The first phase of the Foreign Exchange Liberalization Plan (2002 2005) increased won funding limits for nonresidents and raised the ceiling on the amount of residents' foreign borrowings requiring notification. The 2005 merger of the Korea Stock Exchange, the Korean Securities Dealers Automated Quotation stock market, and the Korea Futures Exchange into the Korea Exchange is expected to upgrade the competitiveness of the nation's trading system for a variety of financial products, including stocks, bonds, options, and other derivatives. There appears to be a natural ordering to the tasks involved: first, establish benchmark bonds and indices; second, develop a diverse derivatives market; third, systematically lengthen the bond market's maturity profile; and fourth, build and develop over-the-counter capability and price structures for derivatives and other complex financial instruments. In developed countries, as banks have become increasingly cautious about extending credit, a gradual process of disintermediation has been occurring in historically bank-oriented financial regimes, fed by considerable regulatory efforts directed at market liberalization.